Provisions of people’s rights in Islamic jurisprudence -Child rights as a model - Khelkhal, Maroua; Sakina, Bouyelli (International Journal of Psychosocial Rehabilitation, 2022)
Childhood is one of man’s most important stages. in which it needs to be cared for and maintained by both existence and non-existence, Preservation of the presence by preserving, caring for and protecting it so that it is a person together and prepared for legitimate costs s belly and provide the necessary care to ensure that he is out of life while fully healthy, In our research, we have tried to demonstrate some of the rights affirmed to the child, but not limited to representation. And we found that the baby is going through three main phases, and it’s just two phases. Non-discrimination, the stage of discrimination, and rights vary from one stage to another, since at the outset it is established that there is an incomplete obligation. This means that certain rights are established exclusively for the foetus, such as the right to descent and inheritance. and when the foetus comes out of life and is alive, it is established that he has full capacity, i.e. that all rights are established for him, In the process of discrimination, the child acquires incomplete performance in order to reduce his or her mind. The purpose of this capacity is to validate some of the beneficial acts or acts between the benefit and the damage that were committed by the distinguished child and the validity of his or her worship, even if they are not answered.